The Uyghur issue in Sino-Central Asian States relations in the post-cold war period - Kasimu, Abulaihaiti (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2010)
This study surveys the Sino-Central Asian States relations with reference to the Uyghur issue. The study answers the following questions: What is the nature of the Uyghur issue? What are China's interests and policies in its relations with Central Asian states with reference to the Uyghur issue? What are Central Asian States' responses towards Chinese policies? Exploring China's interests in Central Asia vis-avis the Uyghur issue, this study argues that the primary concern for China has been the stability in the Xinjiang Uyghur Autonomous Region (XUAR) as evidenced by the policies pursued by the Chinese government in the region since the independence of the Central Asian states. This study has found that the root causes of Uyghur dissent have been the question of legitimacy of Chinese rule in Xinjiang and the regional autonomy policies that have been pursued since 1949 by the People's Republic of China (PRC). This study has also found that the Central Asian States have submitted to all of China's demands of controlling the Uyghur movements in their respective countries; the reason being that the Central Asian States needed China's political and economic assistance and shared with China the challenges of Islamic insurgency and Western democracy.